Pemikiran Ekonomi Islam Zaman Rasulullah - Silaen, Aprilia Putri; Hayati, Fitri; Ginting, Herminaria Br.; Adelia, Intan; Andira, Naufal (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to explore the concept of Islamic economics during the time of the Prophet Muhammad SAW by examining aspects of biography, prophetic leadership, and the main principles of economics applied in the Medina community. Using a qualitative study method based on literature analysis from 30 recent scientific journals, the results of the study show that the Prophet Muhammad was not only a bearer of religious messages, but also a visionary leader who implemented an economic system that was just, based on ethics, and focused on the welfare of the people. Values ​​such as justice in distribution, prohibition of usury practices, protection of property rights, the formation of a healthy market, and management of zakat and baitul maal became the main pillars of the Islamic economic order at that time. This study also evaluates the short-term and long-term impacts of the implementation of this economic thought on the lives of Muslims and on the development of Islamic economic theory in subsequent periods.